A quantitative evaluation of a regional Positive Behavioural Support workforce development approach. Issue 6 (1st July 2021) - McKenzie, Karen; Murray, George; Martin, Rachel; Murray, Aja; Metcalfe, Dale
Abstract: Background: Research suggests that providing staff with input in relation to Positive Behavioural Support (PBS) can have beneficial outcomes. Much of this research, however, fails to take account of systemic issues and does not include a control group. Method: We used a non‐randomised, controlled group design to evaluate accredited PBS programmes, delivered as part of a systemic, regional and workforce development approach. We compared outcomes of those attending the programmes ( n = 240) with a control group ( n = 54), pre‐ and post‐intervention and at 3‐months follow‐up. Results: The programme and its wider impact were rated positively. Significant intervention effects were found for staff practice and retention, but not for staff knowledge and attributions, or behaviours that challenge and quality of life of those being supported. Conclusions: The results are discussed in the context of the study limitations and restrictions resulting from the Covid‐19 pandemic.